2008
DOI: 10.1007/s00234-008-0408-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing brain white matter on sequential cranial ultrasound and MRI in very preterm infants

Abstract: Introduction Periventricular white matter (WM) echodensities, frequently seen in preterm infants, can be associated with suboptimal neurodevelopment. Major WM injury is well detected on cranial ultrasound (cUS). cUS seems less sensitive for diffuse or more subtle WM injury. Our aim was to assess the value of cUS and magnetic resonance imaging (MRI) for evaluating WM changes and the predictive value of cUS and/or MRI findings for neurodevelopmental outcome in very preterm infants with normal to severely abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 33 publications
(101 reference statements)
4
30
0
5
Order By: Relevance
“…showing that infants with normal cUS at term age had normal MRI or only mildly WM abnormalities [8], consistent with the study by Leijser et al [6,7]. A study comparing cUS and MRI showed that inhomogeneous grade I WM echogenicities seen on cUS seem to correlate with subtle white matter abnormalities such as punctuate WM lesions on MRI [9] These two studies have been performed in centres of high expertise in cUS ultrasound performance and interpretation.…”
Section: Horsch Et Al Compared Paired Cus and Conventional Mri Perforsupporting
confidence: 74%
See 2 more Smart Citations
“…showing that infants with normal cUS at term age had normal MRI or only mildly WM abnormalities [8], consistent with the study by Leijser et al [6,7]. A study comparing cUS and MRI showed that inhomogeneous grade I WM echogenicities seen on cUS seem to correlate with subtle white matter abnormalities such as punctuate WM lesions on MRI [9] These two studies have been performed in centres of high expertise in cUS ultrasound performance and interpretation.…”
Section: Horsch Et Al Compared Paired Cus and Conventional Mri Perforsupporting
confidence: 74%
“…Depending on the local settings and the interaction between the neonatologist and radiologist the level of expertise may vary significantly. Poor kappa values in this study suggest that cUS performance and interpretation should be improved by structured and continuous training as other units have shown that cUS well done is effective at detecting abnormality and normality and predicting outcome [5,6,19].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Studies using this protocol [21,22] have demonstrated a higher sensitivity in predicting outcomes than those applying brain US on a less frequent basis [23,24]. Serial US will not miss: (1) periventricular cysts of focal periventricular leukomalacia (PVL), which appear after the first postnatal week, progressively coalesce and then disappear at about term-equivalent age by forming the wall of the lateral ventricles [4,11]; (2) periventricular clastic lesions secondary to sepsis, necrotizing enterocolitis and viral and fungal infections developing any time in the neonatal period [11,[14][15][16]25]; (3) post-haemorrhagic ventricular dilatation that may develop any time after intraventricular hemorrhage [26], and (4) perforator stroke occurring any time after the first week and sometimes affecting the posterior limb of the internal capsule [12].…”
Section: When Do We Perform Us?mentioning
confidence: 99%
“…Periventricular flaring in infants of less than 32 weeks gestation may present ischemic and/or inflammatory damage. 5 When persisting for over one week, and when the echogenicity exceeds that of choroid plexus, flares are considered the first stage of periventricular leukomalacia. 5 MRI is the examination of choice for suspected HIE.…”
Section: Hypoxic-ischemic-encephalopathy (Hie)mentioning
confidence: 99%